Enhancing capacities to understand and implement the International Treaty on Plant Genetic Resources for Food and Agriculture: Report of an International Training Workshop, Tsukuba International Convention Center, Japan, 23–25 October 2013 - Vernooy, Ronnie; Bioversity International (2014)
The report documents a training course on the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) held in Tsukuba, Japan, organized for 15 Asian national ITPGRFA focal points. Topics covered include the rationale and meaning of the core provisions of the ITPGRFA including the use of its Standard Material Transfer Agreement (SMTA); options for national implementation of the multilateral system of access and benefit sharing; options for national protection of Farmers’ Rights; and mechanisms for raising awareness and building capacity.